Phenotype of limited cutaneous systemic sclerosis patients with positive anti-topoisomerase I antibodies: data from the EUSTAR cohort. (28th March 2022) - Zanatta, Elisabetta; Huscher, Dörte; Ortolan, Augusta; Avouac, Jérôme; Airò, Paolo; Balbir-Gurman, Alexandra; Siegert, Elise; Matucci Cerinic, Marco; Cozzi, Franco; Riemekasten, Gabriela; Hoffmann-Vold, Anna-Maria; Distler, Oliver; et al.
Abstract: Objectives: To characterize patients with positive anti-topoisomerase I (ATA) in lcSSc. Methods: SSc patients enrolled in the EUSTAR cohort with a disease duration of ≤3 years at database entry were considered. We assessed the risk of major organ involvement in the following groups: ATA-lcSSc vs ACA-lcSSc and vs ANA without specificity (ANA)-lcSSc, and ATA-lcSSc vs ATA-dcSSc. Cox regression models with time-dependent covariates were performed with the following outcomes: new-onset interstitial lung disease (ILD), ILD progression [forced vital capacity (FVC) decline ≥10% and ≥5% vs values at ILD diagnosis), primary myocardial involvement (PMI), pulmonary hypertension (PH), any organ involvement and all-cause mortality. Results: We included 1252 patients [194 ATA-lcSSc (15.5%)], with 7.7 years (s .d . 3.5) of follow-up. ILD risk was higher in ATA-lcSSc vs ACA- and ANA-lcSSc and similar to ATA-dcSSc, although with less frequent restrictive lung disease. The risk of FVC decline ≥10% (35% of ATA-lcSSc) was lower in ATA-lcSSc than in ATA-dcSSc, whereas FVC decline ≥5% occurs similarly between ATA-lcSSc (58% of patients) and other SSc subsets, including ATA-dcSSc. The risk of PMI was similar in ATA-lcSSc and ANA-lcSSc but lower than in ACA-lcSSc; no difference in PH and mortality risk was observed among lcSSc subsets. The risk of any organ involvement, PMI and PH was lower and the mortality tended to be lower in ATA-lcSSc vs ATA-dcSSc. Conclusion: ATA-lcSSc patients have a high risk of ILD, albeit with a lower risk of progression compared with ATA-dcSSc, supporting careful screening for ILD in this subgroup.